Implementasi Metode Template Matching Pada Kotak Amal - Vharisha, Dhea; Bastomi, Aldi; Saputra, Zanu; Andik Setiawan, I Made (Jurnal Inovasi Teknologi Terapan, 2024)
The charity box is a place to collect alms from the community. Currently, the charity box that we often encounter in the money counting system in the charity box is still required to open the lid of the charity box and count manually. Therefore, a system is needed that can recognize banknote denominations and automatically calculate the nominal amount of banknotes that go into the charity box. The aim of this research is to design and create a system for reading nominal banknotes using a Logitech C3010 webcam and monitoring the number of banknotes using the MIT App Inventor application. In this research, the author uses the template matching method to identify the nominal value of banknotes that go into the charity box. Based on the test results, the template matching method can be implemented to detect nominal banknotes with a threshold value of >0.40 and an effective distance of 20-30 cm so that the nominal money produced is detected very well.